Analisis Pengendalian Persediaan Bahan Baku Pada Perusahaan PT.Kampung Coklat Blitar - Pranowo, Shakila Aprilia; Arfah (Business Administration Dept. - Faculty of Social and Political Sciences, Hang Tuah University, 2025)
This study aims to analyze the inventory control system of cocoa beans at PT Kampung Coklat Blitar and evaluate the implementation of optimal ordering and storage. The research used a qualitative descriptive approach with data collection through interviews, observation, and documentation. The results show that the company orders raw materials routinely without optimal calculation, causing high annual ordering costs and risk of stock shortages. Using the Economic Order Quantity (EOQ) method, the optimal order quantity is 36 tons per transaction, with a frequency of 10 times per year and a savings of Rp16,724,470. The study concludes that EOQ improves inventory efficiency in the company.